Donor/Acceptor‐Stabilized 1‐Silaketene: Reversible [2+2] Cycloaddition with Pyridine and Evolution by an Olefin Metathesis Reaction. Issue 29 (8th June 2016) - Reyes, Morelia Lopez; Troadec, Thibault; Rodriguez, Ricardo; Baceiredo, Antoine; Saffon‐Merceron, Nathalie; Branchadell, Vicenç; Kato, Tsuyoshi
Abstract: The reaction of silacyclopropylidene1 with benzaldehyde generates a 1‐silaketene complex2 by a formal atomic silicon insertion into the C=O bond of the aldehyde. The highly reactive 1‐silaketene2 undergoes a reversible [2+2] cycloaddition with pyridine to give sila‐β‐lactam3 . Of particular interest, in the presence of 4‐dimethylaminopyridine (DMAP), 1‐silaketene complex2 evolves through an intramolecular olefin metathesis reaction, generating a new 1‐silaketene complex8 and cis ‐stilbene. Theoretical studies suggest that the reaction proceeds through the formation of a transient silacyclobutanone, a four‐membered‐ring intermediate, similar to that proposed by Chauvin and co‐workers for the transition‐metal‐based olefin metathesis. Abstract : Atomic silicon insertion : The base‐stabilized silacyclopropylidene behaves as an atomic silicon source leading to a formal atomic silicon insertion into the C=O bond of benzaldehyde. The obtained 1‐silaketene complex evolves through an intramolecular olefin metathesis reaction.